2022
DOI: 10.1002/jmv.28131
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 vaccinations and rates of infections, hospitalizations, ICU admissions, and deaths in Europe during SARS‐CoV‐2 Omicron wave in the first quarter of 2022

Abstract: The vaccination campaigns brought hope to minimizing the coronavirus disease 2019 (COVID‐19) burden. However, the emergence of novel, highly transmissible Omicron lineage of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) and the waning of neutralizing antibodies a few months after vaccination has brought concerns over the vaccine efficacy. The present work analyzed the relationships between COVID‐19 vaccine coverage (completion of primary course and booster dose intake) in the European Economic A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 52 publications
3
11
0
2
Order By: Relevance
“…Looking at the empirical literature dealing with the SARS-CoV-2 pandemic and the ways how to overcome it, one realizes that there does not exist a fully-fledged econometric study analyzing the effects of vaccinations on the infection rate and on the rate of hospitalization, to our knowledge. The study by Rzymski et al (2022) is similar to our study in terms of research objectives. However, they only studied the correlation between the variables (within a shorter time frame) without estimating any econometric specification.…”
Section: Literature On the Effects Of Covid-19supporting
confidence: 65%
See 1 more Smart Citation
“…Looking at the empirical literature dealing with the SARS-CoV-2 pandemic and the ways how to overcome it, one realizes that there does not exist a fully-fledged econometric study analyzing the effects of vaccinations on the infection rate and on the rate of hospitalization, to our knowledge. The study by Rzymski et al (2022) is similar to our study in terms of research objectives. However, they only studied the correlation between the variables (within a shorter time frame) without estimating any econometric specification.…”
Section: Literature On the Effects Of Covid-19supporting
confidence: 65%
“…They draw a trend line through the observed data that suggests a slightly positive relation such that countries with higher a proportion of population fully vaccinated have higher COVID-19 cases per 1 million people. Rzymski et al (2022) examined whether vaccine coverage in the European Economic Community countries are associated with COVID-19 related burden (in terms of infection rates, hospitalizations, admission to intensive care units and deaths), where they considered the wave of the Omicron variant from January to April 2022. They concluded that the vaccination (including boosters) is related to a decreased COVID-19 burden during the first 2 months of 2022.…”
Section: Literature On the Effects Of Covid-19mentioning
confidence: 99%
“…The higher hospitalization, ICU admission, and mortality in OUD patients should be taken into consideration in the vaccination programs. These programs have been implemented globally, and the efficacy of vaccines in terms of all investigated factors (infection, hospitalization, ICU admission, and mortality) has been shown in several studies [57][58][59]. Given the higher COVID-19 complications in OUD cases, preventive measures such as vaccination should be especially considered in them in order to reduce the COVID-19 burden in this highly susceptible population.…”
Section: Discussionmentioning
confidence: 99%
“…Its use was supported by the results of randomized clinical trials proving clinical improvement and shortening the recovery time and mortality rate in patients with mild to moderate course of infection [ 22 , 38 ]. Identifying highly infectious Omicron in late 2021 raised concerns about its impact on the pandemic dynamics and the effectiveness of the vaccines and COVID-19-approved therapies [ 39 , 40 , 41 ]. Based on literature reports of reduced activity of some monoclonal antibodies against this new lineage, some regulatory institutions, e.g., the U.S. Food and Drug Administration (FDA), limited their distribution [ 42 ].…”
Section: Discussionmentioning
confidence: 99%